A chitosan-based coating with or without clove oil extends the shelf life of cooked pork sausages in refrigerated storage. (January 2016) - Lekjing, Somwang
Abstract: Chitosan coatings, with and without clove oil, were investigated for effects on quality and shelf life of cooked pork sausages stored at a refrigerated temperature (4 ± 2 °C). The various treatments of cooked pork sausages were: untreated (control), coating with 2% chitosan (CS), and coating with a mixture having 2% chitosan and 1.5% clove oil (CS + CO). Various microbiological, physical, chemical and sensory properties were monitored over 25 days of storage. The total viable count, the psychrotrophic bacteria count, the L* value, peroxide value and the thiobarbituric acid reactive substances increased, while the a* value, the b* value, the pH and the sensory scores decreased with storage time, across all treatments. However, these changes were slowest with the CS + CO treatment. Based on sensory evaluation and microbiological quality, the shelf lives were 14 days for control, 20 days for CS, and 20 days for CS + CO treated samples, under refrigerated storage. Highlights: Cooked pork sausages were dip coated with a mixture of chitosan and clove oil. The shelf life was assessed with microbiological and sensory quality tests. The coating improved the shelf life by about one third, from 15 to 20 days.